Irony Comprehension In Children With ASD: Does Conventionality Make a Difference? - Carlgren, Hannah M. (My University, 2017)
Irony, a non-literal language convention in which the meaning of the statement and what is said are contradictory, is employed and practiced in the English language regularly. To interpret an ironic statement accurately, an individual must be able to infer the speaker’s meaning, attitude and intent. This type of interpretation is potentially one of the most difficult tasks to develop for children diagnosed with Autism Spectrum Disorder (ASD), as a core deficit of individuals with ASD is perspective taking skills as well as deficits in pragmatic communication. The current study explored the acquisition of irony for children ages eight to eleven years with ASD in comparison to their typically developing same-aged peers, and their peers with language impairments. It will also examine how the conventionality of the ironic statement influences the child’s comprehension skills. The study presented 22 short vignettes to participants via auditory or written modalities. These vignettes contained remarks that were either ironic or literal in nature, and utilized both conventional and situation-specific remarks. Following presentation of the vignette, participants were asked a series of questions to assess their comprehension of speaker meaning, attitude, and intent. Results from the sample of 5 participants indicated that there were no significant differences between the two types of remarks. Implications for those findings are discussed.